Direct Selling Di Era Digital Melalui Online Store Di Media Sosial: Studi Pada Konten Live Streaming Tiktok - Yogie Alontari; Robby Rachman Nurdiantara; Asmarandani Heryadi Putri; Taufiq Furqon Nurhakim (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
The development of internet technology in the digital era, has opened up new opportunities for companies both large scale and small and medium scale or MSMEs in marketing or selling their products to reach customers. One of the latest trends that combine aspects of social media, e-commerce, and direct interaction with consumers is the phenomenon of direct selling through live streaming content on the TikTok, which is carried out by online store account owners to offer their products or services. The researcher intends to find out and analyze how direct selling in the digital era on live streaming content from online stores on TikTok social media and how online stores utilize TikTok for direct selling marketing purposes. This research used qualitative research and using content analysis as the method. The research results showed that the types of products or services offered is fashion, beauty, food and consulting services; the number of viewers in live streaming content varies, from tens of thousands of viewers; the direct interaction aspect between the seller and the audience in direct selling on TikTok is very important; the marketing strategies used are varied; as well as the importance of product quality, product planning and stock management in direct selling practices via live streaming on TikTok. Furthermore, the direct selling process with TikTok social media on live streaming content consists of several stages, namely the product preparation stage, broadcast promotion, conducting live broadcasts, interacting directly with the audience as potential buyers, the product purchase transaction process, the product delivery process by the seller or online store as well as product assessments from buyers (testimonials).